2005
DOI: 10.1007/s11270-005-5417-x
|View full text |Cite
|
Sign up to set email alerts
|

Farm Nutrient Management Practices in Two Geographically Diverse Watersheds in the Cottonwood River Watershed of Minnesota, USA

Abstract: The characteristics of a river are shaped by the quality of the tributaries that flow into it and each of the tributaries in turn reflects the management practices that occur on the soils and landscapes in their drainage areas. In the Cottonwood River of Minnesota, USA and many of its tributaries, nutrient enrichment [primarily nitrogen (N) and phosphorus (P)] and suspended sediments contribute to nonpoint source pollution. Our objective was to assess farm characteristics and nutrient management practices amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2006
2006

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Spatial heterogeneities in the release of nutrients and soil in a watershed can occur due to variations in the application of fertilizer and the degree to which agricultural soils erode. Two sub-watersheds in the Cottonwood River watershed in Minnesota were found to differ considerably in the amount of nitrogen and phosphorus applied to agricultural lands despite similarities in landscape and crop production (Strock et al 2005). A study of an Iowa watershed and two of its subbasins found that the concentration of nitrate was higher in the outlet of the subbasins than in the watershed outlet (Tomer et al 2003).…”
Section: Nutrient Discharge From the Agricultural Midwest And Associamentioning
confidence: 99%
“…Spatial heterogeneities in the release of nutrients and soil in a watershed can occur due to variations in the application of fertilizer and the degree to which agricultural soils erode. Two sub-watersheds in the Cottonwood River watershed in Minnesota were found to differ considerably in the amount of nitrogen and phosphorus applied to agricultural lands despite similarities in landscape and crop production (Strock et al 2005). A study of an Iowa watershed and two of its subbasins found that the concentration of nitrate was higher in the outlet of the subbasins than in the watershed outlet (Tomer et al 2003).…”
Section: Nutrient Discharge From the Agricultural Midwest And Associamentioning
confidence: 99%